Missing: A Private Novel - Patterson, James 1947-; Fox, Kathryn 1966- (New York, NY : Vision, 2017)
Craig Gisto has promised Eliza Moss that his elite team at Private Sydney will investigate the disappearance of her father. After all, as CEO of a high-profile research company, Eric Moss shouldnt be difficult to find--except its not just the man whos gone missing. Despite the most advanced technology at their disposal, they find every trace of him has vanished, too. And they arent the only ones on the hunt.
"This book was previously published as Private Sydney in the UK by Century and in Australia by Century Australia ... in 2015." -- Title page verso.
Keywords: Private investigators -- Fiction; Missing persons -- Fiction; Criminal investigation -- Fiction; Detective and mystery fiction; Thrillers (Fiction)